Child labour an economic perspective - Grootaert, Christiaan; Kanbur, Ravi. (1995)
Child labour is upsetting. The popular images in the developed world are drawn from Dickens and the "dark, satanic mills" of the industrial revolution on the one hand, and the sweatshops and street children of the cities of the developing world on the other. A common, and natural enough, reaction in developing countries has been to enact legislation to ban child labour as did the now-developed world when it emerged from its period of industrialization. Trade sanctions are being recommended in some developed countries against the exports of developing countries which use child labour. Many, including developing country governments, see this as a disguised protectionist device.
Photocopy.
This article is a condensed and edited version of a background paper, "Child labour: a review," prepared for the World Bank's forthcoming World development Report 1995.
Includes bibliographical references (p. 201)
Keywords: Child labor -- Economic aspects